Identification of Camel Skull: Forensic Study - Jain, Payal (Indian Journal of Veterinary Anatomy, 2020)
The skull was incomplete, presented with the lateral half (left) up to the infraorbital foramen over the maxilla. Size of skull was comparatively larger. The most characteristic feature which was recorded and differentiatesit from other two species was absence of facial crest and facial tuberosity over the maxilla bone. Supraorbital foramen was near the frontal suture. Prominent external sagittal crest was also noticed along with the bulged frontal and parietal area. Internally the cranial cavity was divided in to two parts by presence of tentorium cerebella osseum. On the basis of these identical features under examination skull was distinguished it as a camel species.